2020
DOI: 10.3341/kjo.2019.0127
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Ocular Trauma during Eid Festivities in Yemen

Abstract: We sought to elucidate causes of ocular trauma in children younger than 17 years of age during the Eid festivities in Sana'a, Yemen. Methods: A prospective observational case series study was conducted in two tertiary emergency hospitals (Al-Thawra and Magrabi Hospital). The Eid Al-Fitr festive holidays in 2016 lasted 10 days from July 3 to 12. All children up to 17 years of age presenting with ocular trauma were included in the study. All patients underwent detailed history-taking and examination concerning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…In our study, similar to previous studies, 33% of the injuries were caused by active fireworks [17]. In another study, despite the fireworks regulation law, it has been reported that eye injuries are on the rise, especially in relation to the increased use of fireworks during festivals [18]. Similarly, in our study, injuries related to the use of fireworks in weddings and celebrations, which increased in the summer months, were more common.…”
Section: Dıscussıonsupporting
confidence: 90%
“…In our study, similar to previous studies, 33% of the injuries were caused by active fireworks [17]. In another study, despite the fireworks regulation law, it has been reported that eye injuries are on the rise, especially in relation to the increased use of fireworks during festivals [18]. Similarly, in our study, injuries related to the use of fireworks in weddings and celebrations, which increased in the summer months, were more common.…”
Section: Dıscussıonsupporting
confidence: 90%
“…Next in line of frequency were those in the closed globe trauma category, including hyphema and cataracts. In addition, when compared with similar studies, we found conflicting remarks because several studies 1,4,10,23,24,26,28,39 had open globe trauma as the most common outcome from the insult, whereas several others 7,11,19,22,27,29,34,35 reported closed globe trauma to be the case, the most common manifestation of which was hyphema, subconjunctival hemorrhage, and ocular/adnexa contusion.…”
Section: Discussionmentioning
confidence: 78%
“…However, the presence of gun-induced injuries is a matter of deep concern. On the other hand, other studies have vastly contrasting reports, with either blunt [9][10][11]25,36,38 or sharp objects 2,7,31,32 being more common based on the region and the culture of the population the study was conducted on.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All the subjects were males between 4 and 15 years old, and the injuries among the children involved the right eye (52.5%) and the left eye (47.5%). The majority of injuries (n = 152, 95.0%) had occurred in the street, while eight (5.0%) had happened at home, and the most frequent cause of injury was reported to be fireworks mishaps (Aldoais, Bamashmus et al, 2020). The preceding findings indicate that parent loss significantly increased during times of conflict and is substantially connected with child injury.…”
Section: Accidents and Injuriesmentioning
confidence: 88%